The Influence of Leadership, Work Environment, and Organizational Commitment on Organizational Citizenship Behavior (OCB) with Job Satisfaction as an Intervening Variable at PT. Bank Sumut Tebingtinggi Branch - Iskandar, Muhammad; Rahayu, Sri; Robain, Wilchan (Lafadz Jaya Publisher, 2024)
This research aims to determine the influence of leadership, work environment and organizational commitment on Organizational Citizenship Behavior (OCB) with Job Satisfaction as an Intervening Variable at PT. Bank Sumut Tebingtinggi Branch. This research is field research which is carried out directly at the research location or place where the phenomenon being studied occurs. This research uses an associative approach which aims to find relationships or associations between variables. The method used is a quantitative method, where the data collected is in the form of numbers or data that can be calculated. The focus of the research is to examine the influence of independent variables such as Leadership (X1), Work Environment (X2), and Organizational Commitment (X3), the intervening variable Job Satisfaction (Z), and the dependent variable OCB (Y). This research was conducted with a population of 41 employees of Bank Sumut Tebing Tinggi Branch. The results of this research show that leadership, work environment and organizational commitment have a positive influence on Organizational Citizenship Behavior (OCB) at PT. Bank Sumut Tebing Tinggi Branch.